1989
DOI: 10.3109/00016488909127530
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Target of Streptomycin in the Internal Ear

Abstract: The cellular target of streptomycin (STP) was investigated by analyzing the activity of glutamate decarboxylase (GAD) or choline acetyltransferase (ChAT) enzymes of synthesis of GABA and acetylcholine (Ach), respectively, [supposedly located in hair cells (GAD) or efferent terminals (ChAT)] in control and in 50 day-STP-treated colored guinea pig vestibular homogenates. Vestibular and auditory function were assessed by measuring postrotatory nystagmus response (PNR) and auditory brainstem evoked potentials (ABP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 11 publications
2
8
0
1
Order By: Relevance
“…Subsequent studies confirmed and extended these observations in frog (López and Meza, 1988), chick (Meza et al, 1982), rat, and guinea pig (López et al, 1990). Biochemical studies further demonstrated the presence of the GABA synthetic enzyme glutamic acid decarboxylase (GAD) in the labyrinth, even following 8th nerve section (Meza et al, 1982;López and Meza, 1988), and the depletion of GAD following hair cell degeneration (Meza et al, 1989).…”
supporting
confidence: 58%
See 1 more Smart Citation
“…Subsequent studies confirmed and extended these observations in frog (López and Meza, 1988), chick (Meza et al, 1982), rat, and guinea pig (López et al, 1990). Biochemical studies further demonstrated the presence of the GABA synthetic enzyme glutamic acid decarboxylase (GAD) in the labyrinth, even following 8th nerve section (Meza et al, 1982;López and Meza, 1988), and the depletion of GAD following hair cell degeneration (Meza et al, 1989).…”
supporting
confidence: 58%
“…GABA was localized immunocytochemically in both type I and type II hair cells by using several different GABA antibodies in chick (Usami et al, 1987a), chicken (Usami et al, 1989;Matsubara et al, 1995), pigeon (Matsubara et al, 1995), and guinea pig (López et al, 1990; but see Didier et al, 1990, for nonconfirmatory data) but was not observed in hair cells of the squirrel monkey (Usami et al, 1987b;Matsubara et al, 1995). The presence of GAD in both types of hair cells (Usami et al, 1989;López et al, 1992) and the loss of GAD activity following streptomycin-induced hair cell degeneration (Meza et al, 1989) further supported a role for GABA as a hair cell transmitter. However, localization of GABA transaminase, an enzyme responsible for GABA degradation, is less clear; the enzyme has been found in some hair cells (types I and II) and calyces of the guinea pig (López et al, 1992), but only in fibers thought to be afferent processes in chicken (Usami et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…15 '17 In a previous work, isolated vestibular cristae homogenates from 50-day streptomycin (STP) treated guinea pigs showed an 85% decrease of GAD specific activity; 16 choline acetyltransferase (CHAT), that according to our EM immunocytochemical experiments is located in the efferent bouton contacting vestibular receptor cells, 13 was in contrast, not affected. 16 Such evidence is in perfect accordance with a well described selective vestibulotoxic STP action 2'3'6~8'19'23 especially upon the hair cell of vestibular sensory periphery. 5,n,12,24 Our EM observations of degenerated HCI and HCII structure in the above experiments confirm this description.…”
supporting
confidence: 76%
“…Indirect evidence include the gradual increment of GAD activity in vestibular homogenates of developing chick, guinea pigs and rats, as hair cell-afferent junction matures [17][18][19]; in other experiments, GAD activity remained in the epithelium after the vestibular nerve underwent ablation in the frog [20] and the enzyme was depleted when hair cells were destroyed by streptomycin treatment in the guinea pig [21] together could be taken to imply a hair cell localization of GAD. This notion was later confirmed by immunocytochemical localization of this enzyme in the hair cell cytoplasm of vestibular organs in chicks [22] guinea pigs [23,24] and rats [25,26].…”
Section: The Cellular Localization Of Gad Criterionmentioning
confidence: 99%